Orofacial harmonization: analysis of Dentists’ knowledge about clinical risks and legal and ethical aspects in the practice of rhinomodeling and bichectomy (Research, Society and Development, 2021)
Orofacial harmonization consists of making the patient's face more aesthetically acceptable through procedures such as: facial filling with biomaterials, application of botulinum toxin, bichectomy, cervical liposuction and rhinomodeling. The objective of this study is to evaluate the perception of dentists regarding the skills for rhinomodeling and bichectomy procedures regarding the legal support for their performance. After the ethics committee approved this research, a self-administered structured questionnaire with 15 questions about the participant's profile, topics on orofacial harmonization and specific subjects about bichectomy and rhinomodulation, was prepared for the professionals who were willing to participate. Of the 180 questionnaires answered, 105 (58.3%) were from female professionals, 41 (22.9%) said they performed orofacial harmonization procedures in their clinical routine. When asked about being able to treat an already installed nasal necrosis, 19 (11.0%) participants declared that they were able to proceed with this type of treatment, while 110 (72.8%) informed that they would refer this case to a Doctor. It was possible to observed that, in general, professionals are not aware of the norms that support the execution of new procedures included among those traditionally practiced in Dentistry. In addition, from the professionals who attended training courses in Orofacial Harmonization, most of them do not feel confident to perform procedures such as rhinomodeling.